Off the grid [videorecording (DVD)] - Duhamel, Josh, 1972-; Kinnear, Greg, 1963-; Stormare, Peter (Lionsgate, 2025)
After a morally-bankrupt company tries to weaponize a brilliant scientist's revolutionary technology, he goes off the grid to safeguard humanity. When the company sends a strike force to find him, they make their biggest mistake of all, they weaponize the man they are trying to catch. Armed with unrivaled brains and brawn, the wild genius turns Guerilla warfare into a deadly science.